Selective removal of anti-double-stranded DNA antibodies by immunoadsorption with dextran sulphate in a patient with systemic lupus erythematosus. Issue 10 (October 1989) - Kinoshita, M; Aotsuka, S; Funahashi, T; Tani, N; Yokohari, R
Abstract : A dextran sulphate gel column removed anti-double-stranded DNA antibodies (anti-dsDNA) selectively, efficiently, and safely from the circulation of a patient with systemic lupus erythematosus (SLE). The mechanism of the removal is thought to be due to cross reactivity of anti-dsDNA with dextran sulphate, which has negatively charged units. Selective removal of anti-dsDNA is expected to contribute not only to the treatment but also to elucidation of the pathogenesis of SLE.